(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2010)
Global population growth and industrial activities in recent decades has been caused to enter excessive amount of pollutants to water resources. Industrial textile dyes are an important class of the pollutants in the sewage system. Disposal of the dyes in precious water resources must be avoided, however, and for that various treatment technologies are in use. Considering the toxicity of the pollutants, their removal from water resources is necessary. In this research, removal of reactive red 74, RR47, from aqueous solution by zinc oxide nanoparticles was investigated and the affecting parameters such as pH, contact time and adsorbent mass on removal efficiency were determined. Langmuir and Freundlich isotherms were studied and the results indicated that the adsorption process obey the Langmuir and Freundlich isotherms. The experimental results also showed that the pseudo-second order kinetic equation could nicely describe the sorption kinetics.